2003
DOI: 10.1177/1099636203005003002
|View full text |Cite
|
Sign up to set email alerts
|

Theory for Midplane Asymmetric Sandwich Cylindrical Shells

Abstract: In shells, bending stresses in addition to the membrane stresses exist near each structural discontinuity (such as at edge supports, rings, stringers, holes, etc.) and each load discontinuity. This region is the “bending boundary layer”. In sandwich shells, mid-plane asymmetry can be employed to minimize these bending stresses. Governing equations for mid-plane asymmetric sandwich cylindrical shell subjected to axially symmetric loads are derived herein and solved. The solution involves a mid-plane asymmetry f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…This research was concluded by Chen as part of her doctoral dissertation. Other studies associated with the research are given in [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…This research was concluded by Chen as part of her doctoral dissertation. Other studies associated with the research are given in [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…5 Later on, valuable results for elastic behavior of sandwich cylindrical shells were published by Preisner and Vinson. 6 Finally, Jaskula and Zielnica 7 presented an analysis for elasto-plastic stability of sandwich cylindrical panels. In all above reported works, no plastic deformations were allowed in the core of the sandwich shell.…”
Section: Introductionmentioning
confidence: 99%